Detection of Treponema pallidum in blood samples fixed on card for diagnosis of congenital syphilis (Research, Society and Development, 2021)
Congenital syphilis (CS) is a vertically transmitted disease caused by Treponema pallidum causing an infection of the baby in the uterus. Diagnosis of CS is difficult and has been made by a combination of clinical and laboratory criteria, which makes it necessary to search for new diagnostic methods to aid decision making. Molecular tests, despite not being routine in laboratories, are being used more and more. The pre-analytical stage of sample collection, DNA extraction and preservation is essential. The use of fixed blood on a card (SFC) has been an alternative in the diagnosis of various diseases due to the ease of carrying out the pre-analytical stage. Our study aimed to detect T. pallidum by polymerase chain reaction (PCR) from CFS of newborns that had a positive PCR result with the cerebrospinal fluid (CSF) sample. . Eighty-two paired samples (blood and CSF) were analyzed from 41 NB at the Hospital da Criança Santo Antônio (HCSA), in Porto Alegre, RS, Brazil, 22 positive and 19 negative. Sensitivity and specificity were 63.3% and 100%, respectively. The agreement between the methods was substantial (K=0.619), showing that PCR directly from CFS can be promising, as long as it is improved, it is a possibility to diagnose CS and facilitate neonatal screening.